Illustration Of Polyfunctional Properties of Insecticidal Strains Of Bacillus Thuringiensis - Ilkhom, Khalilov; Qalandar, Bababekov; Anvar, Abdullayev; Aziza, Usmonkulova; Maftuna, Qalandarova; Rayimjon, Alamuratov; Murodali, Boboqulov; Zafar, Aliyev (International Journal of Membrane Science and Technology, 2023)
In this study, several economically efficient nutrient media based on local raw materials were selected. Phytohormone synthesis, biomass production, insecticidal activity against the Colorado beetle and effects on plant growth and development in vegetative experiments of Bacillus thuringiensis strains grown in these nutrients were studied. Bacterial strains of Bacillus thuringiensis grown on molasses medium showed the highest insecticidal activity, entomocidal activity was 31.4% on 7 days and 67.4% on 14 days. The average entomocidal activity of B. thuringiensis bacterial strains grown on nonfat dry milk-based medium was 34.5% against the Colorado beetle after 7 days of incubation, and 67.7% by day 14. According to the results of the experiment, it is possible to recommend nutrient media based on molasses and dry milk for the production of biopreparations based on Bacillus thuringiensis bacterial strains.